BIRD DISTRIBUTION IN ITERA CAMPUS AREA BASED ON VALUE CHANGES IN NORMALIZED DIFFERENCE VEGETATION INDEX (NDVI) - Rizki Kurnia Tohir; Mohammad Ashari Dwiputra; Fajar Islam Sitanggang (Department of Forest Resources Conservation and Ecotourism - IPB University, 2021)
Land-use change from a rubber plantation into the ITERA campus area causes an ecological transition. The components of ecology affected are vegetation and wildlife (bird). Geographic information systems can be used to assess the condition of vegetation and its relation to the ecological component. This study analyses bird diversity, vegetation condition through the NDVI value distribution, and then analyses the bird distribution based on vegetation condition. Observation in transect is the method for collecting bird distribution data. Analyses of vegetation condition was carried out based on NDVI. Analyses of bird distribution based on vegetation condition was carried out spatially by overlaying thematic maps of vegetation with bird distribution. This research found 28 bird species belonging to 18 families with diversity index (H’) 1.84. The highest abundance species were Lonchura punctulata, Passer montanus, and Hirundo tahitica. The NDVI values ranged from -0.64-0.87. ITERA vegetation conditions are divided into five classes: very rare vegetation (VRV), rare vegetation (RV), m vegetation (MV), dense vegetation class (DVC), and very dense vegetation (VDV). Total encounters with birds in this study were 753. The distribution of birds to the vegetation conditions in ITERA has a higher tendency and diverse vegetation have implications of birds to use the vegetation. In the VRV class, there were 4 encounters, RV 37, MV 157, DVC 235, and VDV 315. Also, the number of bird species tends to increase along with the increasing vegetation value. Lonchura punctulata is a bird with the highest abundance in each vegetation class, followed by Passer montanus and Pycnonotus aurigaster. Key words: bird distribution, ITERA, land-use change, vegetation condition